STRATEGI EFEKTIF PEMILAHAN SAMPAH UNTUK MEWUJUDKAN LINGKUNGAN BELAJAR YANG BERSIH DI PONDOK PESANTREN AS’ADIYAH PENGKENDEKAN KECAMATAN SABBANG KABUPATEN LUWU UTARA - Haslianti, Haslianti; Ikbal, Ikbal; Wanda, Wanda; A, Nurnaningsih (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Effective waste sorting is an essential factor in creating a clean and healthy learning environment, especially in pondok pesantren with a large number of students. However, challenges still exist in implementing a waste sorting system due to a lack of awareness and inadequate facilities. This community service program aims to design and implement an effective waste sorting strategy at Pondok Pesantren As'adiyah Pengkendekan to improve environmental cleanliness and raise students' awareness of waste management. The activities began with an observation of the cleanliness conditions and the existing waste management system in the pesantren. Subsequently, interviews were conducted with pesantren administrators, students, and educators to identify obstacles and needs in implementing waste sorting. Based on the results of observations and interviews, socialization and education on the importance of waste sorting were carried out, along with the installation of segregated waste bins and training on the management of organic and inorganic waste. The results of this program showed an increase in awareness and participation among pesantren residents in maintaining cleanliness and implementing a more effective waste sorting system. With this program, it is expected that the pesantren can adopt a more efficient waste management system to create a healthier and more comfortable learning environment